Upaya Meningkatkan Kemampuan Sosial Anak Melalui Pendidikan Kewirausahaan pada Kelompok Anak Usia 5-6 Tahun - Fijanatul Karimah (Action Research Journal, 2021)
This research was carried out on the basis of improving social skills in early childhood group B TK Muslimat NU Masyithoh 19 "Annisa" Jenggot Pekalongan through entrepreneurship education. This research is a qualitative descriptive study with data collection techniques sourced from observations, interviews, and documentation. The aim of this research is to describe and analyze social development through entrepreneurship education in early childhood. The results of this study showed that the learning outcomes of group B were initially 35.7% due to a lack of confidence in children in interacting with friends and after corrective actions were carried out using social skills activities through the role of the seller in the center with the results in the first cycle obtained 58.6% while in the second cycle of social skills activities through the role of sellers outside the center obtained about 80%. This shows an increase in social skills learning outcomes through entrepreneurship education conducted in cycles I and II in group B TK NU Masyithoh 19 "Annisa" Jenggot Pekalongan. Based on all classroom action research activities, it can be concluded that the development of the social abilities of children in group B of NU Masyithoh 19 "Annisa" Jenggot Pekalongan Kindergarten in the 2018/2019 Academic Year can be improved through entrepreneurship education.